Development of the Agribusiness Local Content Curriculum in Growing Red Onions Class VII MTs. Muhammadiyah Kalosi Enrekang Regency - Hisanan, Herawan; Abdul Haling; Arnidah, Arnidah; Nurhikmah H; Mohamad Ikbal Riski A. Danial; Abdul Hakim; Mitha Evalista (Cita konsultindo, 2024)
This study is a development research that aims to explore: (1) the need for curriculum development in the local content of agribusiness focused on shallot cultivation for seventh-grade students at MTs. Muhammadiyah Kalosi in Enrekang district, (2) the validation of the learning product content for the Agribusiness Local Content Curriculum in shallot cultivation, and (3) the user responses regarding the practicality of the developed curriculum for seventh-grade students at MTs. Muhammadiyah Kalosi. The research subjects included content experts, media experts, teachers, and students who would be using the developed product. Specifically, the study involved 1 content expert, 1 media expert, 1 local content subject teacher, and 24 seventh-grade students at MTs. Muhammadiyah Kalosi. The research employed a development design adapted from Ken Peffers et al. (2007), which comprises six main activities. However, due to time constraints, the research focused on four activities: 1) identifying problems, 2) determining goals and solutions, 3) designing and developing products, and 4) demonstrating products. A needs assessment was conducted through questionnaires distributed to students and subject teachers, which revealed a strong requirement for a curriculum focused on agribusiness in shallot cultivation for seventh-grade students at MTs. Muhammadiyah Kalosi. The curriculum was validated as both feasible and practical, as evidenced by expert validators, teacher feedback, and group trials, all of which placed it in the